UPLC测定食用油中的3种香兰素类物质含量Determination of three vanillin compounds in edible oil by UPLC - 孟繁磊，张慧，范宏，谭莉，宋志峰 MENG Fanlei, ZHANG Hui, FAN Hong, TAN Li, SONG Zhifeng (Zhongguo youzhi)
为解决现有检测方法存在前处理净化不完全、不彻底的情况，建立了超高效液相色谱（UPLC）测定食用油中香兰素、甲基香兰素和乙基香兰素含量的分析方法。用乙腈提取食用油中目标物，以乙腈饱和的正己烷萃取净化，冷冻分层后，再经Oasis PRiME HLB固相萃取柱净化，采用C18色谱柱分离，以0.5%甲酸水溶液-乙腈为流动相进行UPLC测定，外标法定量。结果表明：3种香兰素类物质在0.1~100.0 mg/L范围内线性关系良好，相关系数大于0.999，检出限均为0.03 mg/kg，定量限均为0.1 mg/kg；在 0.1、0.2、1.0 mg/kg 3个添加水平的平均回收率为86.6%~108.1%，相对标准偏差（RSD）为2.0%～8.8%。同时，采用本方法与BJS 201705中方法对食用油中的3种香兰素类物质进行测定，两种方法结果间无显著性差异。综上，建立的方法采用两步净化，减少了杂质对香兰素类物质的干扰，适用于食用油中香兰素类物质含量的测定。In order to solve the problem of incomplete purification in the pretreatment of the existing testing methods,a method for the determination of vanillin, methyl vanillin, and ethyl vanillin in edible oil by ultra high performance liquid chromatography (UPLC) was established. The target compounds in edible oil sample were extracted with acetonitrile, purified by n-hexane saturated by acetonitrile, frozen and stratified, then extracted and purified by Oasis PRiME HLB column, separated by C18 chromatographic column, and eluted with 0.5% formic acid aqueous solution and acetonitrile as the mobile phase gradient for the UPLC analysis. The external standard method was used for quantification. The results showed that the linearity of the three vanillins was good in the range of 0.1-100.0 mg/L, with correlation coefficient higher than 0.999, the detection limit was 0.03 mg/kg, and the quantitation limit was 0.1 mg/kg.The average recoveries at three additive concentrations of 0.1, 0.2 mg/kg and 1.0 mg/kgwere 86.6%- 108.1%, and the RSD was 2.0%-8.8%. There was no significant difference between the results of the established method and BJS 201705.The established method uses a two-step purification to reduce the interference of impurities to vanillin compounds, and is suitable for the determination of vanillins in edible oil.